Produccion biomasa de Trichoderma harzianum por fermentacion liquida - Garcia, R.=700 1 Duran, M.A.; Riera, R.
(Es, En)
Ilus., 7 ref.
Keywords: TRICHODERMA HARZIANUM; BIOMASA; FERMENTACION; CUBA; FERMENTACION LIQUIDA